2014
DOI: 10.1051/ocl/2013060
|View full text |Cite
|
Sign up to set email alerts
|

Undesirable substances in vegetable oils: anything to declare?

Abstract: The presence of undesirable compounds in vegetable and animal oils and fats may have many different origins. Although the potential toxicity of most of these undesirable compounds is real, poisoning risks are rather limited due to the efficient elimination during oil-refining steps, careful conditioning, choice of efficient packaging and industrial quality control management. However the research of contaminants is part of multiple controls conducted by fat and oil industry to verify the conformity of products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…The higher than grilled and boiled PAHs levels in the fried fish samples may partly be attributed to the penetration and retention of vegetable oil used in frying, and this may lead to the elevation of PAHs beyond background concentration. The presence of PAHs in vegetable oils is as a result of its formation during the drying of seeds used in the production of crude vegetable oils [ 31 , 32 ]. The levels of PAH in edible vegetable oil depends upon the condition under which the refining and deodourisation procedures takes place, and the quality control measure put in place [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher than grilled and boiled PAHs levels in the fried fish samples may partly be attributed to the penetration and retention of vegetable oil used in frying, and this may lead to the elevation of PAHs beyond background concentration. The presence of PAHs in vegetable oils is as a result of its formation during the drying of seeds used in the production of crude vegetable oils [ 31 , 32 ]. The levels of PAH in edible vegetable oil depends upon the condition under which the refining and deodourisation procedures takes place, and the quality control measure put in place [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Charcoal grills were reported to result in higher PAHs levels compared with oven grills. Oven grill and boiling can also results in variable PAHs levels depending of the temperature achieved, circulation of air and the grilling/boiling time [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Along the supply chain, vegetable oils can be contaminated by various components, including phthalates (Lacoste, 2014). A 2009 study reported a concentration of 43 ppm of di-2-(ethylhexyl) phthalate (DEHP) in a walnut oil sample (Lacoste, 2014). Phthalates are dialkyl or alkyl aryl esters of phthalic acid commonly used as additives to increase the flexibility of plastic materials.…”
Section: Introductionmentioning
confidence: 99%
“…The role of the exporter is to define the smallest batch that he would eliminate in case of problem. For example, if a batch of palm oil is contaminated with polycyclic aromatic hydrocarbons (PAHs; Lacoste, 2014), the exporter could remove a batch of containers, a pallet or a silo, and this will not cost the same of course. When a product presents a little risk, the batch layout will be necessarily larger.…”
Section: The Eu Legal Framework On Traceabilitymentioning
confidence: 99%